Sosialisasi Pencegahan Covid Melalui Penerimaan Vaksin Covid-19 Di Kecamatan Tebet Jakarta Selatan - Trimawartinah Trimawartinah; Bunga Meilinda Nuryono; Elsa Safitri; Putri Khaerunisa (Jompa Abdi: Jurnal Pengabdian Masyarakat, 2022)
Corona Virus Disease that has come to Indonesia cause respiratory system infections and death. COVID-19 is a new variant of disease that has never been identifies before in human body. Most of the cases that reported by the Ministry of Health in 2020 shows symptoms and clinical indication so that people are encouraged to follow the health protocols. Currently, the government is trying to develop vaccines to be more effective for preventing the infection of corona virus. COVID-19 vaccine is a good news for everyone, but there are some Indonesian people that still not willing to be vaccinated. The method of activity is involving stakeholders through the implementation of meeting activities consisting of community leaders and cadres. This action has the aim of persuading the community to implement the health protocols properly. Public needs to get the knowledge and information through education indirectly. The information that will be delivered are about the results of socialization and the explanations of educational material. The socialization that will be doing by the team is by implementing the identification of the survey results. The participants were attending by association, the representative of district, and the head of youth organization in some regions in South Jakarta. This service activity gave a conclusion that Community service activities are well-implemented where the target is to provide the understanding about the Covid-19 prevention behavior and public acceptance of vaccines. Furthermore, publics has given a good response regarding the socialization of providing knowledge to the community